The Pathogen-Occupied Vacuoles of Anaplasma phagocytophilum and Anaplasma marginale Interact with the Endoplasmic Reticulum - Truchan, Hilary K.; Cockburn, Chelsea L.; Hebert, Kathryn S.; Magunda, Forgivemore; Noh, Susan M.; Carlyon, Jason A. (Frontiers in Cellular and Infection Microbiology, 2016)
The genus Anaplasma consists of tick-transmitted obligate intracellular bacteria that invade white or red blood cells to cause debilitating and potentially fatal infections. A. phagocytophilum, a human and veterinary pathogen, infects neutrophils to cause granulocytic anaplasmosis. A. marginale invades bovine erythrocytes. Evidence suggests that both species may also infect endothelial cells in vivo. In mammalian and arthropod host cells, A. phagocytophilum and A. marginale reside in host cell derived pathogen-occupied vacuoles (POVs). While it was recently demonstrated that the A. phagocytophilum-occupied vacuole (ApV) intercepts membrane traffic from the trans-Golgi network, it is unclear if it or the A. marginale-occupied vacuole (AmV) interacts with other secretory organelles. Here, we demonstrate that the ApV and AmV extensively interact with the host endoplasmic reticulum (ER) in endothelial, myeloid, and/or tick cells. ER lumen markers, calreticulin and protein disulfide isomerase, and the ER membrane marker, derlin-1, were pronouncedly recruited to the peripheries of both POVs. ApV association with the ER initiated early and continued throughout the infection cycle. Both the ApV and AmV interacted with the rough ER and smooth ER. However, only derlin-1-positive rough ER derived vesicles were delivered into the ApV lumen where they localized with intravacuolar bacteria. Transmission electron microscopy identified multiple ER-POV membrane contact sites on the cytosolic faces of both species’ vacuoles that corresponded to areas on the vacuoles’ lumenal faces where intravacuolar Anaplasma organisms closely associated. A. phagocytophilum is known to hijack Rab10, a GTPase that regulates ER dynamics and morphology. Yet, ApV-ER interactions were unhindered in cells in which Rab10 had been knocked down, demonstrating that the GTPase is dispensable for the bacterium to parasitize the ER. These data establish the ApV and AmV as pathogen-host interfaces that directly engage the ER in vertebrate and invertebrate host cells and evidence the conservation of ER parasitism between two Anaplasma species.